Annotated checklist and illustrated key to braconid parasitoids (Hymenoptera, Braconidae) of economically important fruit flies (Diptera, Tephritidae) in Brazil - Marinho, Cláudia F.; Costa, Valmir A.; Zucchi, Roberto A. (Zootaxa, 2018)
The braconid parasitoids of fruit-infesting flies have been more intensively studied from the middle to late 1990s, when taxonomic research was restarted in Brazil. At the same time, efforts toward the biological control of fruit flies intensified, and an exotic species, Diachasmimorpha longicaudata, was introduced. In the decade 2010, another exotic species, Fopius arisanus, was introduced, and two new species of Doryctobracon were described. Currently, 12 species of braconids from the subfamilies Alysiinae (two species) and Opiinae (10 species) are associated with fruit flies of economic importance in Brazil, two of which are introduced species. More than half of the species belong to the genus Doryctobracon, with D. areolatus (Szépligeti) the most widely distributed species in Brazil.